A new cyclopentylidene and other chemical constituents from Malaysian Crotalaria pallida - Siti Rabeah Fadzil; Yap, Ann-Chee; Choo, Yeun-Mun (Penerbit Universiti Kebangsaan Malaysia, 2017)
Crotalaria pallida Aiton is an herbaceous legume from the family Fabaceae. In the present study, one new cyclopentyliene, crotolidene (1) and seven known compounds, i.e. hydroxydihydrobovolide (2), octacosane (3), trans-phytyl palmitate (4), linoleic acid (5), methyl oleate (6), ethyl palmitate (7), and palmitic acid (8) were isolated from the C. pallida collected from Perak, Malaysia. These compounds were isolated and characterized using extensive chromatographic and spectroscopic methods.